Bidding on a Peer-to-Peer Energy Market: An Exploratory Field Study - Wörner, Anselma; Tiefenbeck, Verena; Wortmann, Felix; Meeuw, Arne; Ableitner, Liliane; Fleisch, Elgar; Azevedo, Inês (Information Systems Research, 2022)
Moving toward sustainable energy systems to address climate change is one of the key challenges of our generation. To that end, investments in renewable energy and balancing renewable supply and energy demand on the larger scale are crucial. One mechanism to create price signals for demand balancing, as well as for consumer engagement, is to establish trading platforms (or peer-to-peer (P2P) markets) through which households can directly buy and sell renewable energy. However, residential consumers are typically lay users with little or no previous exposure to the complexity and the dynamics involved in energy markets. More so, empirical research on consumer engagement in the energy sector indicates that individuals tend to act against their stated proenvironmental intentions and to lose interest in energy management systems particularly quickly—calling into question regulatory efforts to foster P2P markets to push the transition to renewable energy. We have implemented the first empirical study worldwide that analyzes bidding behavior in a real-world P2P energy market, in which users bid for solar energy via an auction mechanism. For the duration of an entire year, users could interact with the market using a web app. The prices settled on the P2P market directly impacted participants’ electricity bills. We provide unique empirical evidence showing that (1) participants were willing to engage in energy trading and that (2) they understood the market mechanism surprisingly well and exhibited learning effects. Still, bidding behavior did not reflect their stated intention of paying a price premium for local solar energy. The market outcomes reveal that P2P energy markets can indeed have a positive impact on balancing demand and supply, thereby addressing the fundamental challenge of distributed renewable energy systems.<br
Keywords: green IS; P2P markets; electronic markets; market design; sustainable energy systems